Beauty from ashes / Eugenia Price. - Price, Eugenia (Doubleday, 1995)
A historical tale of the Old South featuring Anne Fraser, a widow whose family is split by the Civil War. While she favors the Union, the children favor the Confederacy. Final volume in the Georgia Trilogy which began with Bright Captivity.